Career Choices, Occupational Status, and Quality of Life of Agricultural Science Graduates - Simon, Maria Sheila D. (JPAIR Institutional Research, 2016)
While it seems easy to choose from among the many academic programs available to the person, he has to be very careful in his choice because it may affect the kind of life he will have in the future. The study aimed to determine the career choices, occupational status and quality of life of Agricultural Science graduates. Using descriptive correlational research design, data were obtained from 337 total population graduates of Capiz State University, Pontevedra Campus, Philippines. Questionnaires - checklist were personally delivered, and sent either regular or electronic mail. Frequency count, percentage, ranking and mean were used in the analysis of descriptive data while Chi-square was employed as inferential analysis. Results showed that graduates' career choices relate to occupational status. Moreover, the standard of living is parallel with their perceived quality of life. The university student services office may develop a scheme in assisting students to decide which career to pursue based on their abilities and inclinations. A study on the employability of graduates can be undertaken to verify further and validate the findings.
Keywords: Management; career choices; descriptive correlational research design; Roxas City; Philippines